Integrated Photonic Platform for Robust Differential Refractive Index Sensor - Andre L. Moras; Valnir C. S. Junior; Mario C. M. M. Souza; Giuseppe A. Cirino; Antonio A. G. Von Zuben; Luis A. M. Barea; Newton C. Frateschi (IEEE Photonics Journal, 2020)
We demonstrate an integrated photonic platform comprising a refractive index (RI) sensor based on Photonic Molecule (PM) that effectively mitigates the influence of environmental perturbations using a differential measurement scheme while providing high quality-factor (Q) resonances. The RI sensor consists of a partially unclad microdisk resonator coupled to an external clad microring resonator fabricated on silicon-on-insulator (SOI) platform. We report a RI sensitivity of 24 nm/RIU, achieving a limit of detection (LOD) of 1.7 × 10−3 refractive index units (RIU) with improved stability for an operation range of 0.15 RIU in a compact footprint of 40 × 40 µm2, representing an important solution for real-life applications in which measurement conditions are not easily controllable.